Greek Tragedy and Modernist Performance - Taxidou, Olga (Edinburgh University Press, 2025)
This book examines the ways the encounters between modernist theatre makers and Greek tragedy were constitutive in the modernist experiments in performance. Through a series of events / instances / poses that engage visual, literary and performing arts, the modernist love/hate relationship with classical Greek tragedy is read as contributing to a modernist notion of theatricality, one that follows a double motion, revising both our understanding of Greek tragedy and of modernism itself. Isadora Duncan, Edward Gordon Craig, T.S. Eliot, Ezra Pound, W. B. Yeats, H. D, and Bertolt Brecht and their various, sometimes successful sometimes failed experiments in creating a modernist aesthetic in performing, dancing, translating, designing Greek tragedies, sometimes for the stage and sometimes for the page, are presented as radical experiments in and gestures towards the autonomy of performance. In the process the artists of the theatre themselves – the actor, the designer, the director, the playwright – are reconfigured and given a lineage and genealogy, through this modernist revision of tragedy and the tragic not as as a philosophical or philological tradition, but as a performance practice.